Developmental Pathways From Childhood Aggression–Disruptiveness, Chronic Peer Rejection, and Deviant Friendships to Early‐Adolescent Rule Breaking. Issue 2 (18th November 2014) - Ettekal, Idean; Ladd, Gary W.
Abstract : Childhood aggression–disruptiveness (AD), chronic peer rejection, and deviant friendships were examined as predictors of early‐adolescent rule‐breaking behaviors. Using a sample of 383 children (193 girls and 190 boys) who were followed from ages 6 to 14, peer rejection trajectories were identified and incorporated into a series of alternative models to assess how chronic peer rejection and deviant friendships mediate the association between stable childhood AD and early‐adolescent rule breaking. There were multiple mediated pathways to rule breaking that included both behavioral and relational risk factors, and findings were consistent for boys and girls. Results have implications for better understanding the influence of multiple social processes in the continuity of antisocial behaviors from middle childhood to early adolescence.